2014
DOI: 10.1080/01635581.2014.894094
|View full text |Cite
|
Sign up to set email alerts
|

Lithocarpus Polystachyus Rehd Leaf Aqueous Extract Inhibits Human Breast Cancer Growth In Vitro and In Vivo

Abstract: Lithocarpus polystachyus leaves have been used as tea beverage and folk medicine for healthy care in the Southwest of China. The purpose of this study is to investigate the anticancer activity of Lithocarpus polystachyus Rehd leaf aqueous extract (LPAE) and to explore the possible mechanism of its activity. Growth inhibition effects of LPAE breast cancer were tested in vitro and in vivo. The possible mechanism of its activity was analyzed with cell biological and molecular biological assays. After LPAE treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…The crude extract was partitioned between water and ethyl acetate, and the ethyl acetate soluble fraction was separated by repeated column chromatography. As a result, four new triterpenoids (1)(2)(3)(4), three triterpenoids [3,4-seco-4(23),20(29)-lupadiene-3,28dioic acid (5), 3,4-seco-olean-4(23),12-diene-3,28-dioic acid (6), and 3,4-seco-ursan-4(23),12-diene-3,28-dioic acid (7)] were isolated for the first time from a natural source [12,13] (▶ Fig. 1), and six known compounds [3-epi-betulinic acid (8), betulinic acid (9), betulonic acid (10), cylicodiscic acid (11), lupeol (12), and 3epi-glutinol (13)] were identified [14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crude extract was partitioned between water and ethyl acetate, and the ethyl acetate soluble fraction was separated by repeated column chromatography. As a result, four new triterpenoids (1)(2)(3)(4), three triterpenoids [3,4-seco-4(23),20(29)-lupadiene-3,28dioic acid (5), 3,4-seco-olean-4(23),12-diene-3,28-dioic acid (6), and 3,4-seco-ursan-4(23),12-diene-3,28-dioic acid (7)] were isolated for the first time from a natural source [12,13] (▶ Fig. 1), and six known compounds [3-epi-betulinic acid (8), betulinic acid (9), betulonic acid (10), cylicodiscic acid (11), lupeol (12), and 3epi-glutinol (13)] were identified [14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…The obvious differences between them were the 1 H and 13 C NMR shifts of C-3 in 3β,20-dihydroxylupane-28-oic acid (δ H 3.55, t, J = 9.0 and δ C 78.3) slightly changed in 2 (δ H 3.61, t, J = 4.0 and δ C 75.3), which suggested that 2 is a stereoisomer of 3β,20-dihydroxylupane-28-oic acid. In the COSY spectrum, the three proton sequences H 2 -1 (δ H 1 Fig. 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menurut studi literatur terhadap spesies yang berbeda dari tumbuhan ini memiliki berbagai macam aktivitas. Daun dari tumbuhan Lithocarpus polystachus Rehd memiliki aktivitas antidiabetes (Dong et al, 2012), aktivitas antioksidan (Sun et al, 2015) dan antikanker (Lin et al, 2014), Lithocarpus celebicus memiliki aktivitas antimikroba (Khan et al, 2001).…”
Section: Pendahuluanunclassified
“…Likewise, bioactivities from the genus have been evaluated including antioxidants, antidiabetic, anticancer, antimicrobial and other activities. [5][6][7][8] In regard to explore antidiabetic agent from Talang Mamak medicinal plants 9 , we reported the antioxidant and antidiabetic activity of L. bancanus leaves extract and fractions.…”
Section: Introductionmentioning
confidence: 99%